REMARKABLE RESULT TOWARDS RETINOPATHY ASSOCIATED AUTOIMMUNE HEMOLYTIC ANEMIA - Rofa Husnul Khuluqi; Nadia Artha Dewi; Susanto Nugroho; Lely Retno Wulandari (International Journal of Retina, 2022)
Introduction: To present the clinical findings of Autoimmune hemolytic anemia (AIHA) Retinopathy and its rapid resolutions following treatment with steroid. Case report: A 14-year-old female patient presented with decreased vision in the left eye. There was history of AIHA. Visual acuity was 1/60 in LE and 6/6 in RE. There was conjunctival pallor, and the other anterior segment were unremarkable. Fundus examination of left eye revealed flame shaped and dot blot hemorrhage, roth’s spots, optic disc swelling, venous turtuosity, and elevated macula. There were afferent pupil defect, red green deficiency, and contrast sensitivity decline. Hematological evaluation revealed anemia. A MRI Head and Orbital examination were unremarkable. Discussion: This patient was assessed with LE Anemic retinopathy due to AIHA. The patient’s visual acuity improved as the retinopathy resolved after 1 month of oral steroid therapy. Conclusion: Anemia may play a role in the occurrence of retinopathy. The diagnosis of retinopathy can be made by linking ophthalmic fndings with positive serological test. Accurate comprehensive examination can establish the systemic diagnosis, and control of systemic parameters will improve retinopathy, reverse vision loss, and avoid permanent blindness